Whole-Process Pollution Control for Cost-Effective and Cleaner Chemical Production—A Case Study of the Tungsten Industry in China. (August 2019) - Cao, Hongbin; Zhao, He; Zhang, Di; Liu, Chenming; Lin, Xiao; Li, Yuping; Ning, Pengge; Sun, Jiajun; Zhang, Yi; Sun, Zhi
Abstract: In this research, a methodology named whole-process pollution control (WPPC) is demonstrated that improves the effectiveness of process optimization. This methodology considers waste/emission treatment as a step of the whole production process with respect to the minimization of cost and environmental impact for the whole process. The following procedures are introduced in a WPPC process optimization: ① a material and energy flow investigation and optimization based on a systematic understanding of the distribution and physiochemical properties of potential pollutants; ② a process optimization to increase the utilization efficiency of different elements and minimize pollutant emissions; and ③ an evaluation to reveal the effectiveness of the optimization strategies. The production of ammonium paratungstate was chosen for the case study. Two factors of the different optimization schemes—namely the cost-effectiveness factor and the environmental impact indicator—were evaluated and compared. This research demonstrates that by considering the nature of potential pollutants, technological innovations, economic viability, environmental impacts, and regulation requirements, WPPC can efficiently optimize a metal production process.